CHOROIDAL ALTERATIONS IN ABCA4-RELATED RETINOPATHY. Issue 2 (February 2017) - Müller, Philipp L.; Fimmers, Rolf; Gliem, Martin; Holz, Frank G.; Charbel Issa, Peter
Abstract : Purpose: To investigate choroidal alterations in ABCA4 -related retinopathy. Methods: Mean choroidal thickness and subfoveal choroidal thickness were measured in the right eyes of 40 patients with ABCA4 -related retinopathy using enhanced-depth imaging optical coherence tomography. The right eyes of 65 age-matched healthy subjects were used for comparison. Results: Compared with controls, patients with ABCA4 -related retinopathy revealed a reduced subfoveal choroidal thickness ([mean ± SEM] 347 ± 10 μ m vs. 302 ± 12 μ m; P = 0.006) and mean choroidal thickness (315 ± 9 μ m vs. 275 ± 10 μ m; P = 0.005). This difference was mainly due to choroidal thinning in eyes with reduced photopic and/or scotopic amplitudes on full-field electroretinography. Atrophy of the retinal pigment epithelium (RPE) was associated with a thinner choroid compared with eyes without RPE atrophy (subfoveal choroidal thickness: 277 ± 17 μ m vs. 341 ± 16 μ m; mean choroidal thickness: 252 ± 13 μ m vs. 313 ± 13 μ m; both, P ⩽ 0.001), but choroidal thinning was not restricted to the area of RPE atrophy. Choroidal thickness was similar to controls when RPE atrophy and functional loss were limited to the central retina. There was no association between visual acuity and choroidal thickness. Conclusion: The results indicate choroidal alterations in widespread ABCA4 -related retinopathy, especially when associated with atrophy of the RPE. The absence of focal choroidal thinning in areas of RPE atrophy is suggestive for a diffusible factor from the RPE sustaining the choroidal structure. Abstract : Supplemental Digital Content is Available in the Text.Choroidal thickness in ABCA4 -related retinopathy may be normal when disease is restricted to the macula and is reduced in patients with retina-wide disease manifestation. Choroidal thinning is associated with the presence of RPE atrophy, although a direct topographic relation is lacking.